2003
DOI: 10.1097/00006231-200307000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid scintigraphy with 99mTc-MIBI and 123I subtraction: a comparison with magnetic resonance imaging and ultrasonography

Abstract: The aim of this study was to evaluate the efficacy of 99mTc-MIBI and 123I subtraction scintigraphy for the detection of abnormal parathyroid glands to be referred for surgical treatment. Thirty-nine consecutive patients, including 35 primary and four secondary cases of hyperparathyroidism, were evaluated. 99mTc-MIBI/123I subtraction scintigraphy (MIBI/I) was performed on all patients, and the results were compared with delayed images of 99mTc-MIBI (D-MIBI), magnetic resonance imaging (MRI) and ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 17 publications
3
28
1
3
Order By: Relevance
“…102 In general, the sensitivity of MRI for localizing hyperfunctioning parathyroid glands ranges from 43 to 71%, higher when it is employed for detecting ectopic glands (88-96%). 103,104 A more recent study demonstrated that high-resolution MRI using a 3.0 T magnet could detect adenomas in 57% of patients with PHPT in whom both contrast CT and 99m Tc-sestamibi scintigraphy failed to localize the adenoma. 105 MRI protocols involve multiplanar acquisition images of the neck and upper mediastinum.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…102 In general, the sensitivity of MRI for localizing hyperfunctioning parathyroid glands ranges from 43 to 71%, higher when it is employed for detecting ectopic glands (88-96%). 103,104 A more recent study demonstrated that high-resolution MRI using a 3.0 T magnet could detect adenomas in 57% of patients with PHPT in whom both contrast CT and 99m Tc-sestamibi scintigraphy failed to localize the adenoma. 105 MRI protocols involve multiplanar acquisition images of the neck and upper mediastinum.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…It is possible to use positron emission tomography in combination with CT to detect the hyperfunctioning gland, but this is not yet widely implemented [13]. Magnetic resonance imaging is another possible imaging modality with a reported sensitivity rate of 43.4–57.1% [14,15]. Ultrasound (US) is quick, non-invasive and does not require the use of radioactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…After its introduction in 1989 (4), Tc-sestamibi (MIBI) rapidly became the radiopharmaceutical of choice for the identification and location of abnormal parathyroid glands (5,6), using single photon emission computed tomography (SPECT). In addition, MIBI scintigraphy is characterized by higher sensitivity and specificity compared with morphological techniques such as ultrasonography, magnetic resonance and computed tomographic imaging (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%